Study on Expansion Characteristics and Expansion Potential of Gypsum Rock. (14th October 2022) - Fu, Junfu; Li, Huayun; Zhu, Kaicheng; Chen, Yelei; Lei, Zhongcheng
Abstract : In this study, the relationship between four expansion indices and the expansion potential of gypsum rock was studied; on this basis, a criterion for judging expansion potential is established for gypsum rock. The results show that the free expansion rate is unsuitable for grading gypsum rocks' expansion potential. Setting the gypsum rock in the Wuzhishan tunnel as the research subject, the ultimate expansion rate is 24.28% on the 7th day and 34.08% on the 30th day; the ultimate expansion rate on the 7th day of the indoor rock sample can be estimated by the fitting formula on the 30th day, the ultimate expansion force is 304.51 kPa, and the BET-specific surface area is 6.31 m 2 /g. The ultimate expansion ratio and BET-specific surface area have an excellent linear relationship with the ultimate expansion force. Setting the ultimate expansion force, ultimate expansion ratio and BET-specific surface area as the standard, the criterion for judging the expansion potential of gypsum rock is determined, which is more convenient and accurate than existing standards. The standard in this paper can predict the potential disasters that may occur in underground engineering.